Metformin Promotes the Protection of Mice Infected With Plasmodium yoelii Independently of γδ T Cell Expansion - Miyakoda, Mana; Bayarsaikhan, Ganchimeg; Kimura, Daisuke; Akbari, Masoud; Udono, Heiichiro; Yui, Katsuyuki (Frontiers in Immunology, 2018)
Adaptive immune responses are critical for protection against infection with Plasmodium parasites. The metabolic state dramatically changes in T cells during activation and the memory phase. Recent findings suggest that metformin, a medication for treating type-II diabetes, enhances T-cell immune responses by modulating lymphocyte metabolism. In this study, we investigated whether metformin could enhance anti-malaria immunity. Mice were infected with Plasmodium yoelii and administered metformin. Levels of parasitemia were reduced in treated mice compared with those in untreated mice, starting at approximately two weeks post-infection. The number of γδ T cells dramatically increased in the spleens of treated mice compared with that in untreated mice during the later phase of infection, while that of αβ T cells did not. The proportions of Vγ1+ and Vγ2+ γδ T cells increased, suggesting that activated cells were selectively expanded. However, these γδ T cells expressed inhibitory receptors and had severe defects in cytokine production, suggesting that they were in a state of exhaustion. Metformin was unable to rescue the cells from exhaustion at this stage. Depletion of γδ T cells with antibody treatment did not affect the reduction of parasitemia in metformin-treated mice, suggesting that the effect of metformin on the reduction of parasitemia was independent of γδ T cells.